Seroprevalence of Zika in Brazil stratified by age and geographic distribution - Botosso, Viviane Fongaro; Precioso, Alexander Roberto; Wilder-Smith, Annelies; Oliveira, Danielle Bruna Leal de; Oliveira, Fabyano Bruno Leal de; Oliveira, Cairo Monteiro De; Soares, Camila Pereira; Oliveira, Lucyana Trindade Leal; Santo, Ralyria Mello Vieira dos; Utescher, Carla Lilian de Agostini; Coutinho, Francisco Antonio Bezerra; Massad, Eduardo (Epidemiology and infection, 2023)
Congenital Zika is a devastating consequence of maternal Zika virus infections. Estimates of age-dependent seroprevalence profiles are central to our understanding of the force of Zika virus infections. We set out to calculate the age-dependent seroprevalence of Zika virus infections in Brazil. We analyzed serum samples stratified by age and geographic location, collected from 2016 to 2019, from about 16,000 volunteers enrolled in a Phase 3 dengue vaccine trial led by the Institute Butantan in Brazil. Our results show that Zika seroprevalence has a remarkable age-dependent and geographical distribution, with an average age of the first infection varying from region to region, ranging from 4.97 (3.03-5.41) to 7.24 (6.98-7.90) years. The calculated basic reproduction number, , varied from region to region, ranging from 1.18 (1.04-1.41) to 2.33 (1.54-3.85). Such data are paramount to determine the optimal age to vaccinate against Zika, if and when such a vaccine becomes available.
Gesehen am 13.03.2024